ANALISIS LAPORAN KEUANGAN MENGGUNAKAN RASIO LIKUIDITAS PADA PT FAJAR ALAM SCIENTIFIC BANDUNG (PERIODE 2018–2020) - Muthia Fanny Febrianty (Program Studi Ilmu Administrasi Bisnis FISIP UNPAS, 2022)
This research aims to determine the financial condition and determine the liquidity level of PT. Fajar Alam Scientific Bandung. Based on the results of research that PT. Fajar Alam Scientific Bandung experienced problems in the company's financial condition and fluctuating liquidity levels, which was marked by a decrease in cash and fluctuations in current assets and short-term debt during the 2018-2020 period. Thel research methodl used in this research isl descriptive quantitative researchl method. The datal analysis technique usedl comparative analysis and liquidityl ratio lanalysis. Based onl the resultsl of researchl using thel calculation of the liquidity ratio, it shows thatl the company is in a liquid condition in the calculation of the quick ratio, cash ratio, and inventory to net working capital which means the company is in a good or healthy condition and can pay the company's short-term debt on time. The factors that affect the liquidity level at PT. Fajar Alam Scientific Bandung is some receivables have not been paid by consumers in high amounts, there is no implementation of receivables policy, financial management at the company is considered not good in managing company finances so that there is an increase in short-term debt followed by a decrease in cash, and the company is still unable to manage their cash well. Keywords: Liquidity